Analysis of Demand and Estimation of Market Structure of Beef Trading Business in Bandar Lampung City - Muhiddin Sirat; Emi Maimunah; Utami Syifana Widyastuti; Ratna Ermawati; Muhammad Mirandy Pratama Sirat; Deris Desmawan (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
Aims of this study were 1) to determine the effect of beef price, other goods prices, and consumer tastes on the amount of beef demand and 2) to determine the market structure of the beef trade industry in Bandar Lampung City. The analytical method used was multiple linear regression with variables : the beef price of, other goods price, and consumer tastes. The variable price of beef has a t-statistic value (2.222) The variable price of other goods has a t-statistic value (2.379)> t-table (1.664) and the consumer taste variable has a t-statistic value (9,565) > t-table (1.664). The three variables have a t-statistic value > t-table (1.664) and the results of F-statistics (33.884) > F-table (2.49), so the results of this study indicate that together the variable price of beef, the price of other goods and consumer tastes have a positive and significant effect on beef demand in Bandar Lampung City and based on the results of the Relative Mean Deviation Intercept on beef trade in the market of Bandar Lampung City by 44.23%, with the rule of decision 42.54%, The market structure of the beef trading business in the Bandar Lampung City market is classified as a Monopolistic Competition Market